Totally implantable venous access devices: A fifteen-year single-center experience - Kılıç, Berkay; İlhan, Burak; Karanlık, Hasan (The European Research Journal, 2025)
Objectives: Totally implantable venous access devices (TIVADs) are frequently used in cancer patients, offering significant comfort and advantages. This study aims to evaluate the outcomes of patients who underwent port catheter placement. Methods: Data from 3,774 patients who underwent venous port catheter placement between 2007 and 2022 were reviewed. Demographic information, primary diagnoses, port placement locations, number of punctures, complications, and reasons for removal were recorded. Results: The median age of the patients was 54 years (range: 18-86 years). Catheters were placed on the right side in 3,667 patients (97.2%). The most commonly used vessel was the right subclavian vein, accessed in 2,494 patients (66.1%). Complication rates were observed as follows: femoral vein (40%), brachial vein (20%), subclavian vein (12.1%), internal jugular vein (9.9%), and external jugular vein (6.5%). The complication rate following a single puncture was 7.4%, compared to 16.1% for multiple punctures, showing a significant increase with the number of punctures (P=0.03). The most common early complication in 142 (3.8%) patients was arterial puncture with bleeding or hematoma, while the most common late complication was catheter infection of 1.4% (n=54). Conclusions: Venous port catheter placement is generally safe, with the right subclavian vein being the most commonly used site. Ultrasound-guided placement reduces complications, which are more frequent with multiple punctures and left-side placements. Early complications like arterial puncture were more common, while late complications were primarily catheter infection.